2014
DOI: 10.1186/1472-6882-14-189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red pitaya juice supplementation on cardiovascular and hepatic changes in high-carbohydrate, high-fat diet-induced metabolic syndrome rats

Abstract: BackgroundThe fruit of Hylocereus polyrhizus, also known as red pitaya, and buah naga in Malay, is one of the tropical fruits of the cactus family, Cactaceae. Red pitaya has been shown to protect aorta from oxidative damage and improve lipid profiles in hypercholesterolemic rats probably due to phytochemicals content including phenolics and flavonoids. The aim of this study was to investigate the changes in cardiac stiffness, hepatic and renal function in high-carbohydrate, high-fat diet-induced obese rats fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
2
43
3
1
Order By: Relevance
“…The identification of the fruit was done by a botanist from Biodiversity Unit, Institute of Biosciences, Universiti Putra Malaysia. The voucher number is SK-2440/14 as previously described in Ramli et al [ 17 ]. Dragon fruits were freshly harvested when reaching full ripening stage, 35–38 days after pollination, and immediately transported to the Nutritional Laboratory, Faculty of Medicine and Health sciences, Universiti Putra Malaysia.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of the fruit was done by a botanist from Biodiversity Unit, Institute of Biosciences, Universiti Putra Malaysia. The voucher number is SK-2440/14 as previously described in Ramli et al [ 17 ]. Dragon fruits were freshly harvested when reaching full ripening stage, 35–38 days after pollination, and immediately transported to the Nutritional Laboratory, Faculty of Medicine and Health sciences, Universiti Putra Malaysia.…”
Section: Methodsmentioning
confidence: 99%
“…Carotenoid concentration was low in purple carrot juice, so anthocyanins might be the main contributor of antioxidant and anti-inflammatory properties to improve cardiovascular function. In the study of Ramli et al [94], it was demonstrated that consuming red pitaya juice could reduce diastolic stiffness of the heart in rats. Aditionally, blood pressure downregulation effect of Carica papaya fruit juice was examined in male albino Wistar rats [95].…”
Section: Mechanisms Of Action Of Juice On Cardiovascular Diseasesmentioning
confidence: 99%
“…8 Moreover, epidemiological studies have shown that consumption of high-fat and high fructose diets is correlated with high rates of overweight, central obesity and metabolic syndrome. [9][10][11] In addition, further studies have reported that the high fructose-rich diet are usually associated with cardiac alterations by inducing excessive body weight gain, hyperlipidemia, glucose intolerance, hyperinsulinemia, oxidative stress and even atherosclerosis. 12,13 Commonly, statins represent the most widely prescribed hypolipidemic drugs in the world, which is intended for reducing the cholesterol levels in the blood by inhibiting the enzyme HMG-CoA reductase.…”
Section: Introductionmentioning
confidence: 99%